The EXPLORING THE ROLE OF AQUATIC ACTIVITIES IN ENHANCING SOCIAL-EMOTIONAL DEVELOPMENT IN HYPERACTIVE CHILDREN - Wiji Lestari, Shabrina; Fauzi, Rizal Ahmad; Alif, Muhammad Nur (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Children with hyperactivity conditions, often known as ADHD (Attention Deficit Hyperactivity condition), frequently struggle with socialization and emotional regulation. This results from a failure to pay attention to and comprehend social norms. Therefore, strategies are required to address these issues, including the use of aquatic or water-based physical activities. This study will further investigate the function of water activities in enhancing hyperactive children's social and emotional development. Eight participants, three hyperactive kids, three parents of hyperactive kids, and two swimming coaches, were included in this study, which was conducted at one of the Cilacap Regency swimming pools using a qualitative case study methodology. Data triangulation, which included field observations, interviews, and documentation, was used to acquire the data. Using the NVivo 15 pro tool, data analysis was completed by classifying and coding significant themes as research results. Important discoveries have emerged about the function of aquatic activities, their effects, hyperactive children's social interactions, and the methods trainers employ to enhance their social and emotional development. According to Erik Erikson's theory of social-emotional development, aquatic activities help hyperactive kids develop socially and emotionally by promoting energy management, emotion regulation, more focus, social interaction, and coach strategies like play media, regular evaluation, and individualized approaches. Parents, trainers, educators, and even therapists will learn from this study about the advantages of aquatic activities to promote hyperactive kids' social and emotional growth.